O jogo como estratégia para facilitar o ensino de sistema digestório no ensino médio - Caldeira, Daniel de Assis (2019)
Making the class interesting is one of the greatest challenges for teachers, especially with the influence the vast amount of outside stimulus has on the student today. The teaching process is linked to the role of the teacher as a socializing agent and a promoter of the search for knowledge. The National Common Curricular Base encourages the production of varied teaching tools that can benefit learning and make it meaningful and enjoyable for the student. As play activities do not involve pressure, they have high motivating power and generates an environment conducive to learning, being possibly used in the most different moments, to start a topic, as a way to improve knowledge retention or even to evaluate the learning process. These playful-nature activities at schools increase the cognitive development, foster the resolution of problems, the interaction, the cooperation, the immersion in the content, sharpen the curiosity, enhancing the construction of the knowledge. Bearing in mind the difficulties and lack of interest of students in class, the objective of this paper was to build a board game to help the teaching of the digestive system in high school, facilitating and motivating the development of this content and contributing to a more dynamic class. The intention of the game was to approach the physiology and anatomy of the digestive system, as well as subjects related to this system that are of interest to young people, through information contained in cards and by generating discussion among team members. The game will be available on educational websites in print and play format, being a unique way of starting the studies of human physiology and a useful educational tool for the teaching of digestive system in high school. Key-words: teaching, learning, game, digestive system.